1976
DOI: 10.1007/bf00234931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulation of the midbrain reticular formation upon thalamo-cortical neurones responsible for cortical recruiting responses

Abstract: 1. In lightly nembutalized cats, effects of high frequency (60-100/sec) repetitive stimulation of the midbrain reticular formation (RF) were tested upon the thalamo-cortical (T-C) neurones which project from the anterior ventral (VA) nucleus of the thalamus and its vicinities to the parietal association cortex and convey impulses responsible for cortical recruiting and spindling-like responses. 2. Tonic maintained or rhythmic grouped firings of the T-C neurones recorded as extracellular units with microelectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Stimulation of the cMRF has been shown to hyperpolarize ventral thalamic neurons projecting to the motor cortex (Yasuda and Shimono, 1978) or posterior parietal cortex (Sasaki et al, 1976), and result in desynchronization of cortical EEG in rats. Cholinergic input to the thalamus, largely from the PPN (Fitzpatrick et al, 1989), results in prolonged depolarization of thalamo-cortical neurons (Fitzpatrick et al, 1989, Raczkowski and Fitzpatrick, 1989, Steriade et al, 1990, Curro Dossi et al, 1991, McCormick, 1992, Steriade et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the cMRF has been shown to hyperpolarize ventral thalamic neurons projecting to the motor cortex (Yasuda and Shimono, 1978) or posterior parietal cortex (Sasaki et al, 1976), and result in desynchronization of cortical EEG in rats. Cholinergic input to the thalamus, largely from the PPN (Fitzpatrick et al, 1989), results in prolonged depolarization of thalamo-cortical neurons (Fitzpatrick et al, 1989, Raczkowski and Fitzpatrick, 1989, Steriade et al, 1990, Curro Dossi et al, 1991, McCormick, 1992, Steriade et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is how extracortical structures contribute to the EEG arousal. In particular, the thalamic nuclei may switch the neuronal devices in the cerebral cortex on or off according to their own activities or those in the brainstem structures (Ammaro and SAITO, 1966;PURPURA et al, 1966;MANCIA et al, 1974;SASAKI et al, 1976;STERIADE and HOBSON, 1976). These actions would be reflected indirectly in the activities of cortical neurones, but could hardly be examined at present.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated by SASAKI et al (1976) that the ascending reticular activating system suppresses, by means of initial inhibition and later tonic maintained excitation, rhythmic grouped discharges of the superficial T-C neurones which are responsible for synchronized activities of the parietal association cortex, and that the suppression thus result in desynchronization of the cortex. In the present study of the T-C neurones projecting on to the frontal motor cortex, it was found that high-frequency stimulation of RF exerted predominantly inhibitory influences upon the B-group (superficial T-C) neurones and facilitatory influences upon many of the A-group (deep T-C) neurones.…”
Section: Discussionmentioning
confidence: 99%